Large scale meta-analysis characterizes genetic architecture for common psoriasis associated variants - Lam C. Tsoi (Nature Portfolio, 2017)
Psoriasis is an immune-mediated skin disease with a complex genetic architecture. Here, Elder and colleagues identify 16 novel psoriasis susceptibility loci using GWAS meta-analysis with a combined effective sample size of over 39,000 individuals.